Geometrical product specifications (GPS). Acceptance and reverification tests for coordinate measuring systems (CMS). Coordinate measuring machines (CMMs) using single and multiple stylus contacting probing systems using discrete point and/or scanning measuring mode Part 5, (21st April 2020) - British Standards Institution,
No abstract available